Hubungan Penerimaan Diri Dengan Tingkat Kecemasan Pada Wanita Menghadapi Masa Menopause Di Pekon Wates Timur - Agustina, Devita; Putri, Riska Hediya; Kameliawati, Feri; Surmiasih (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Introduction : Menopause is the permanent cessation of menstruation due to the loss of follicular activity in the ovaries, which causes psychological changes, sleep disturbances, and anxiety. Adjusting to oneself is a form of self-acceptance. 61.1% of women experiencing menopause have poor self-acceptance, while 38.9% have good self-acceptance. One of the levels of anxiety in women facing unprecedented situations is anxiety levels, with the majority experiencing moderate anxiety (78.4%) and mild anxiety (21.6%). This study aims to determine the relationship between self-acceptance and anxiety levels in facing menopause.Objective : The effect of providing health education using booklets on the knowledge of pregnant women in handling emergencies for the fetus and pregnant women in the working area of the Sukaraja Health Center in Bandar Lampung City in 2025 is known. Method: This study employed quantitative research, using an analytical survey design and a cross-sectional approach. The population was 70 women facing menopause aged 45-55, using a total sampling technique. Data were analyzed using the Gamma test. Results: The results of the study showed a significant relationship between self-acceptance and anxiety levels in women facing menopause, with a p-value of <0.002 <0.05. Women entering menopause can experience increased anxiety levels. Conclusion: It is hoped that there will be participation from the community health center in providing education about menopause, so that they can monitor the impact of a lack of self-acceptance.